Increased Macrophage-Specific Arterial Infiltration Relates to Noncalcified Plaque and Systemic Immune Activation in People With Human Immunodeficiency Virus. (20th July 2022) - Toribio, Mabel; Wilks, Moses Q; Hedgire, Sandeep; Lu, Michael T; Cetlin, Madeline; Wang, Melissa; Alhallak, Iad; Durbin, Claudia G; White, Kevin S; Wallis, Zoey; Schnittman, Samuel R; Stanley, Takara L; et al.
Abstract: Background: Persistent immune activation is thought to contribute to heightened atherosclerotic cardiovascular disease (ASCVD) risk among people with human immunodeficiency virus (PWH). Methods: Participants (≥18 years) with or without human immunodeficiency virus (HIV) and without history of clinical ASCVD were enrolled. We hypothesized that increased macrophage-specific arterial infiltration would relate to plaque composition and systemic immune activation among PWH. We applied a novel targeted molecular imaging approach (technetium-99m [ 99m Tc]–tilmanocept single photon emission computed tomography [SPECT]/CT) and comprehensive immune phenotyping. Results: Aortic 99m Tc-tilmanocept uptake was significantly higher among PWH (n = 20) than participants without HIV (n = 10) with similar 10-year ASCVD risk ( P = .02). Among PWH, but not among participants without HIV, noncalcified aortic plaque volume related directly to aortic 99m Tc-tilmanocept uptake at different uptake thresholds. An interaction ( P = .001) was seen between HIV status and noncalcified plaque volume, but not calcified plaque ( P = .83). Systemic levels of caspase-1 ( P = .004), CD14 – CD16 + (nonclassical/patrolling/homing) monocytes ( P = .0004) and CD8 + T cells ( P = .005) related positively and CD4 + /CD8 + T-cell ratio ( P = .02) inversely to aortic 99m Tc-tilmanocept uptake volume. Conclusions: Macrophage-specific arterial infiltration was higher among PWH and related to noncalcified aortic plaque volume only among PWH. Key systemic markers of immune activation relating to macrophage-specific arterial infiltration may contribute to heightened ASCVD risk among PWH. Clinical Trials Registration: NCT02542371. Abstract : CD206 + macrophage-specific arterial infiltration (via 99m Tc-tilmanocept SPECT/CT) was higher among participants with vs without HIV and relates to noncalcified plaque (and not calcified plaque) among people with HIV. NLRP3 inflammasome activation, nonclassical monocytes, and T-cell senescence related to CD206 + macrophage-specific arterial infiltration.